PERANAN MULTIMEDIA UNTUK LAYANAN BERKESULITAN MENGGUNAAN KONJUNGSI PADA WACANA NARASI DALAM MENINGKATKAN HASIL BELAJAR - -, Munir; Darmawan, Deni; Supriadie, Didi; Margana, Achmad (Universitas Pendidikan Indonesia, 2017)
Learners Characteristics is part of the area of learning technology . The purpose from learning technology are solving learning problems. In the face of a learning problem students are competencies required of teachers . This research is background characteristics of students when learning in the classroom , including learning difficulty in the use of conjunctions or conjunctive in narrative texts. In this case it requires the handling of teachers in order to increase learners in study. This research was conducted in class VI ( six ) elementary school Sukahurip 01 Subdistrict of Cigedug regency of Garut with a total of 33 study subjects indicated learners learning difficulty. This research is purpose to find a teaching model to provide learning services for students with learning difficulty in the use of conjunctions or conjunctive in narrative texts. This research was conducted to determine : a. the role of multimedia to students' learning difficulty in using of conjunctions or conjunctive in narrative texts in elementary school of Sukahurip 01 Subdistrict of Cigedug. b .Know the role of multimedia for learning difficulty in using of conjunctions in narrative texts can improve student achievements in elementary school of sukahurip 01 the districts of Cigedug. The research method using action research through qualitative descriptive method . Descriptive qualitative method is a method used to know the diagnostic model and service that are used to cope with student' learning difficulty. The results of this researchs are a. Implementation of diagnosis of learning difficulty are data collection , data processing , identifications the factors cause learning difficulty in the use of conjunctions in narrative texts b . model of service learning is implemented through three stages are questionnaire , pretest and posttest.